The development of an electronically operated water control system incorporating a major theme of inclusive design : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Product Development at Massey University - Kersley, Andrew Hilton (Massey University, 2005)
This case study followed the development of an electronically operated water control system, using a structured product development process and incorporating a major theme of inclusive design. Three project objectives were identified for this project: 1. Use the Product Development Process to successfully develop an electronically operated water control system to a stage that is near ready for manufacture. 2. To understand and implement an inclusive design approach to the development of an electronically operated water control system to ensure that the product is usable by people regardless of age or ability. 3. To understand to what effect design decisions, related to the usability of a product, have upon the desirability of the product to all users. The product development process used in the development of this product was successful. It resulted in an innovative new product idea that has associated intellectual property, currently under patent application. The product was identified as both usable to people with a wide range of impairments and desirable to a majority of all potential users. The research methodology relating to inclusive design resulted in the finding that some design decisions relating to the usability of products do in fact affect the desirability of the product to other potential users, and hence could potentially affect the financial success of the product. A set of activities were identified from the process used in this case study and recommended for further product development projects, which will help to ensure that the product is made more usable while still retaining its desirability. KEYWORDS Product Development Process, New Products, Inclusive Design, Consumer Based Design, Successful Products, Elderly and Disabled.
Keywords: Electronic control; Self-help devices; Faucets -- Design; People with disabilities